2010
DOI: 10.1111/j.1399-0004.2010.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Two percent of patients suspected of having Angelman syndrome have TCF4 mutations

Abstract: The TCF4 gene encodes a basic helix-loop-helix (bHLH) transcription factor which belongs to the family of E-proteins. E-proteins form homo- and heterodimers with other members of the HLH family and bind to the common DNA sequence called E-box. Haploinsufficiency of the TCF4 gene has been found to be associated with the Pitt-Hopkins syndrome (PTHS). PTHS is characterized by severe mental retardation, a wide mouth plus other distinctive facial features (fleshy lips, beaked nose, broad nasal bridge) and breathing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 19 publications
4
61
0
2
Order By: Relevance
“…Previous studies have provided clues that TCF4 may be a candidate gene for intelligence. For example, it was found that haploinsufficiency of TCF4 may induce PittHopkins syndrome that is characterized by severe mental retardation (Flora et al, 2007), and that mutations in the TCF4 gene are linked to other types of mental retardation, such as Pitt-Hopkins and Angelman syndromes (Kalscheuer et al, 2008;Takano et al, 2010). Quednow et al (2011) also found a moderate effect of rs9960767 on years of education in patients (although not in controls).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided clues that TCF4 may be a candidate gene for intelligence. For example, it was found that haploinsufficiency of TCF4 may induce PittHopkins syndrome that is characterized by severe mental retardation (Flora et al, 2007), and that mutations in the TCF4 gene are linked to other types of mental retardation, such as Pitt-Hopkins and Angelman syndromes (Kalscheuer et al, 2008;Takano et al, 2010). Quednow et al (2011) also found a moderate effect of rs9960767 on years of education in patients (although not in controls).…”
Section: Discussionmentioning
confidence: 99%
“…TCF4 is critical for normal brain development (Flora et al, 2007). Human haploinsufficiency of TCF4 may result in severe cognitive deficiency (ie, mental retardation) in patients with Pitt-Hopkins syndrome (Pitt and Hopkins, 1978) or Angelman syndrome (Takano et al, 2010). However, the role of the TCF4 gene in cognitive deficiency in SCZ patients has seldom been studied (for exceptions, see Lennertz et al (2011); Quednow et al (2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous hypomorphic, null mutations or deletion (haploinsufficiency) of the TCF4 gene in humans causes the rare PTHS -an autosomal-dominant neurodevelopmental disorder characterized by severe mental, motor and language retardation, epilepsy, facial dysmorphisms, intermittent hyperventilation, and rarely also postnatal microcephaly -, pointing to the fact that TCF4 is critical also for normal development of the mammalian nervous system ( which displays a similar phenotype as PTHS and also have mutations in the TCF4 gene [136]. A recent study with 10 young PTHS patients revealed strong intellectual and motor disabilities together with a behavioral phenotype that overlaps with autism spectrum disorders [137].…”
Section: Tcf4 and Neurodevelopmental Disordersmentioning
confidence: 99%
“…Some of these behaviours may be consistent with the definition of an autism spectrum disorder (ASD). [11][12][13]15 To our knowledge there have been no investigations of cognition, behaviour, and autism in PTHS to date. Here we report an exploratory investigation of behaviour, adaptive, and cognitive functioning in 10 individuals with molecularly confirmed classic PTHS, with the specific aim of exploring the hypothesis that PTHS may be characterized by differing degrees of severity of ASD.…”
Section: Abbreviationsmentioning
confidence: 99%
“…The dominant form of PTHS is caused by deletions ⁄ mutations in Transcription Factor 4 (TCF4) on chromosome 18 at 18q21. [6][7][8][9][10][11][12][13][14] Recessive forms of a PTHS-like disorder are caused by mutations in NeuReXiN1 (NRXN1) on chromosome 2 and CoNTactiN Associated Protein-like 2 (CNT-NAP2) on chromosome 7. 15,16 As studies of the syndrome have accumulated, it has become clear that not all individuals with molecularly confirmed alterations show intermittent overbreathing.…”
mentioning
confidence: 99%